Thin clients and computers' recycling - García, Pablo (2011)
This document shows the achieved results in the installation and testing of thin clients' networks (TCN), arranged with obsolete computers. This research topic arises from previous investigations and it is framed in a wider project which includes the use and compatibility of free and/or open source software (FLOSS1). In this paper, details of how the network was implemented are given; a list of specifications with minimal parameters for a suitable use in classroom is proposed; actions which improve the operation and some of the achieved results in the evaluation of the network are showed as well.